2016
DOI: 10.1016/j.jsps.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Serum TNF-α, GTH and MDA of high-fat diet-induced obesity and obesity resistant rats

Abstract: Among rats fed with high fat diet, in comparison with weight of obesity resistant rats and control group rats, there is no statistically significant difference, (P > 0.05). However, high fat diet will impact mechanisms in vivo in rats, which then induces oxidative stress response and inflammatory response in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 1 publication
6
15
0
Order By: Relevance
“…It was also observed that the hyperlipidemia regulated activity of SCU may be correlated with the hepatic blood flow and liver function. Nguyen [ 38 ] reported that hepatic fatty acids regulated overall lipid metabolism by binding nuclear receptors that modulate gene transcription, consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…It was also observed that the hyperlipidemia regulated activity of SCU may be correlated with the hepatic blood flow and liver function. Nguyen [ 38 ] reported that hepatic fatty acids regulated overall lipid metabolism by binding nuclear receptors that modulate gene transcription, consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, no significant changes in MDA levels were observed in other studies. However, it is important to emphasize that the feeding time was longer (six months) and the composition of the diet was different in these studies, which indicates that the type of diet, as well as the feeding time, are important to induce changes in OS markers such as MDA levels [53].…”
Section: Discussionmentioning
confidence: 95%
“…Numerous scientific studies demonstrate that the use of a high-fat diet (especially long-term) impairs antioxidant defence mechanisms and leads to oxidative stress in the body [ 7 , 8 ]. Excessive fat intake results in mitochondrial β-oxidation of free fatty acids and excessive electron flow involving cytochrome c oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports indicating that excessive fat consumption and obesity adversely affect the nervous system, increasing the risk of dementia and Alzheimer’s disease [ 5 , 6 ]. Impaired functioning of the body due to a high-fat diet is believed to result from the excessive production of reactive oxygen species (ROS) that accompany it [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%